Revolutionizing X-ray technology through the power of computer algorithms - Lee, Ren Hao (Nanyang Technological University, 2022)
X-ray technology has become an integral part of modern-day society, having applications across multiple industries. However, manipulation of X-rays has always been difficult due to their high penetration properties. Reflection of X-ray only occurs at minute angles and the percentage reflected is not significant enough for many applications. In this paper, methods to enhance the performance of X-rays are investigated. The use of multilayer materials such as superlattices improves reflectivity by making use of alternating materials to create multiple reflections within the structure itself. The overall reflectivity is obtained from the sum of these individual reflections. The resultant reflectivity is thereby much higher compared to using a single material, as a portion of the transmitted X-rays is reflected. In addition, computational techniques were applied to identify the best combination of parameters to obtain optimal reflectivity. Three different multilayer structures were chosen, each representing a particular region in the X-ray spectrum. Graphical analysis was first conducted to identify the impact of different parameters on the overall reflectivity of the structure. Using the analysis results obtained, a heuristic search algorithm such as Genetic Algorithm was applied to optimize the peak and mean reflectivity of the three chosen structures separately.